(untitled) (Journal of Education and Development, 2020)
Children with learning disabilities are not only falling behind academically, they are also falling behind emotionally and socially, which is extremely important. This places a strong emphasis on a need for early intervention programs for children with learning disabilities to address these emotional and social deficits. The purpose of this study was to assess the effectiveness of the Better Emotional and Social Times (B.E.S.T.) program offered by the Learning Disabilities association of Niagara Region (LDANR), which targeted areas of self-advocacy, self-esteem, self-understanding (mindfulness), emotional regulation and social skills. Seven children between the ages of 6 and 11 enrolled in the program were closely observed for eight weeks and pre- and post- child interviews and observational checklists were completed throughout the duration of the program by the facilitators as well as the parent/caregivers. Results indicated that all of the children had improved and gained new skill sets in all of these areas. Overall, these results have positive implications, as this type of intervention can be implemented within education policy to ensure children with learning disabilities are receiving the proper aid in regards to these emotional and social deficits, which will also have a positive impact on their literacy deficits as well.